2009
DOI: 10.18061/1811/36606
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the Beat: An Experience-dependent Complex Integration of Multisensory Information Involving Multiple Levels of the Nervous System

Abstract: In a series of studies we have shown that movement (or vestibular stimulation) that is synchronized to every second or every third beat of a metrically ambiguous rhythm pattern biases people to perceive the meter as a march or as a waltz, respectively. Riggle (this volume) claims that we postulate an "innate", "specialized brain unit" for beat perception that is "directly" influenced by vestibular input. In fact, to the contrary, we argue that experience likely plays a large role in the development of rhythmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Instead, the low-tone benefit observed here could be explained by a greater recruitment of brain structures involved in movement planning and control, including motor cortical regions ( 37 42 ), the cerebellum, and basal ganglia ( 24 ). These structures may be recruited via functional interconnections between the ascending auditory pathway and a vestibular sensory-motor network (including a striatal circuit involved in beat-based processing) that is particularly responsive to bass acoustic frequencies ( 43 45 ). The involvement of these sensory-motor areas thus constitutes a plausible mechanism for the observed low-tone benefit, as these areas have been shown to be critically involved in predictive beat perception ( 42 ), to contribute to the selective enhancement of EEG responses at the beat frequency ( 24 ), and to be activated by vestibular input ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, the low-tone benefit observed here could be explained by a greater recruitment of brain structures involved in movement planning and control, including motor cortical regions ( 37 42 ), the cerebellum, and basal ganglia ( 24 ). These structures may be recruited via functional interconnections between the ascending auditory pathway and a vestibular sensory-motor network (including a striatal circuit involved in beat-based processing) that is particularly responsive to bass acoustic frequencies ( 43 45 ). The involvement of these sensory-motor areas thus constitutes a plausible mechanism for the observed low-tone benefit, as these areas have been shown to be critically involved in predictive beat perception ( 42 ), to contribute to the selective enhancement of EEG responses at the beat frequency ( 24 ), and to be activated by vestibular input ( 43 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that direct activation of the human vestibular organ by bass sounds occurs only at higher intensities (above ∼95-dB sound pressure level) than those employed in the current study ( 46 ). However, functional interactions between auditory and vestibular sensory-motor networks in response to low-frequency rhythms can arise centrally ( 45 ). These neural connections presumably develop from the onset of hearing in the fetus through the continuous experience of correlated auditory and vestibular sensory-motor input (e.g., the sound of the mother’s footsteps coupled with walking motion) ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More critically it was demonstrated that head movement and therefore activation of the vestibular apparatus was necessary to observe the effect (Phillips-Silver and Trainor, 2007 ), and further that vestibular influence could be achieved directly by using galvanic vestibular stimulation (Trainor et al, 2009 ). However, the matter remains controversial, with some authors suggesting that the vestibular influence is not direct (Trainor, 2007 ; Riggle, 2009 ; Trainor and Unrau, 2009 ).…”
Section: Subsequent Developmentsmentioning
confidence: 99%
“…The plausibility of this interpretation is enhanced by a recent demonstration that not only actual movement involving the head but also rhythmic electrical stimulation of the vestibulum (which induces apparent head movement) has a comparable effect on rhythm perception and recognition (Trainor, Gao, Lei, Lehtovaara, & Harris, 2009). Trainor et al explicitly hypothesized that auditory signals are enhanced through multisensory integration with vestibular signals in the posterior parietal cortex (see also Trainor & Unrau, 2009). It should be noted, however, that the recognition choices in these studies never included the original ambiguous rhythm.…”
Section: Previous Relevant Researchmentioning
confidence: 99%